2015
DOI: 10.1111/jcpt.12340
|View full text |Cite
|
Sign up to set email alerts
|

Systemic sclerosis and calcinosis cutis: response to rituximab

Abstract: Results of therapy with rituximab on regression/improvement of systemic sclerosis-related calcinosis are limited and non-conclusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…For example, Moazedi-Fuerst et al [164] observed the resolution of calcinosis cutis in three patients with SSc after six months of rituximab 500 mg on day 0 and day 14, and then twice every three months, with no relapse after 1-2 years follow-up, suggesting the efficacy of B-cell depletion therapy as an option in the treatment in these patients. Similarly, other authors reported the efficacy of low-dose rituximab (four weekly infusions of 375 mg/m 2 ) on calcinosis cutis in SSc patients [160,161,165,171]. On the contrary, evidence on DM/JM-related calcinosis cutis is limited and non-conclusive.…”
Section: The Potential Role Of Immunosuppressive Therapiesmentioning
confidence: 93%
“…For example, Moazedi-Fuerst et al [164] observed the resolution of calcinosis cutis in three patients with SSc after six months of rituximab 500 mg on day 0 and day 14, and then twice every three months, with no relapse after 1-2 years follow-up, suggesting the efficacy of B-cell depletion therapy as an option in the treatment in these patients. Similarly, other authors reported the efficacy of low-dose rituximab (four weekly infusions of 375 mg/m 2 ) on calcinosis cutis in SSc patients [160,161,165,171]. On the contrary, evidence on DM/JM-related calcinosis cutis is limited and non-conclusive.…”
Section: The Potential Role Of Immunosuppressive Therapiesmentioning
confidence: 93%
“…A recent case report of a 16-year-old JDM patient with calcinosis and skin ulcerations showed complete resolution without radiologic progression or new lesions after 3 months of abatacept. 107…”
Section: Abataceptmentioning
confidence: 99%
“…Among them, conservative treatments such as medication and follow-up observation are ineffective, and laser or cryotherapy are prone to recurrence [ 23 ]. Therefore, surgical treatment is more often used to excise the diseased tissue intact, and direct suturing, transfer of tipped flaps, and free skin pieces can be chosen according to the skin defect [ 15 , 19 , 24 ]. In this case, the lesion was large and multiple hard nodes were fused into a block, but the lesion was located in the middle and upper part of the scrotum, and the lower part of the skin was intact and the scrotal skin was more extensible, so direct suture was used to close the skin.…”
Section: Discussionmentioning
confidence: 99%